Hotel Portofino. Season two [videorecording (DVD)] - Baker, Matt (Screenwriter) (PBS Distribution, 2023)
It is the summer of 1927 and Bella Ainsworth is still devoting her considerable energies to the Hotel Portofino, which has overcome its early troubles and is starting to prosper.